The Predictive Relationship of Health Related Quality of Life on Objectively-Measured Sleep in Children: A Comparison Across BMI Ranges - Lin, Yi-Ching (Frontiers in Neuroscience, 2019)
ABSTRACT Sleep is considered a major factor related to children’s general quality of life regarding their health outcomes, general well-being, and daily life functions. Kid-KINDL, a health-related quality of life (HRQOL) measure, was used in a consecutive 12-week longitudinal study to compare the association between children’s quality of life (QoL) and sleep duration across different BMI ranges. To reduce recall bias, each child wore an electronic pedometer on their wrist to record their sleep duration. The Pearson χ2 test, one-way analysis of variance (ANOVA), and mixed effect repeated measures analysis were used to investigate the association between children’s QoL and their sleep duration. The original QoL scores showed that underweight children had lower emotional, family relationship, friendship, and school-related scores, and that overweight children had lower physical satisfaction and self-esteem scores. Emotional (beta=-0.3, p<0.01) and family relationships (beta =0.20, p=0.01) significantly influenced the sleep duration of underweight children. The score of emotional well-being decreased by 0.3, the sleep duration will increase by an hour. The poor the emotion well-being children had, the longer they slept. The score of family well-being increased by 0.2, the sleep duration will increase by an hour. The better family quality children had, the longer the slept; For overweight children, the score of family well-being increased by 0.08, the sleep duration will increase by an hour (beta =0.08, p =0.04). Their sleep got longer when they have better family quality. Also, physical and school satisfaction scores significantly affected the sleep duration of obese children. When the score of physical and school increased by 0.09, the sleep duration will increase by an hour (beta =0.09, p =0.01; beta =0.09, p<0.01 respectively). The better the quality of physical condition and school life was, the longer sleep they would get. This study might be the first longitudinal study to evaluate the relationship between QoL and sleep duration, using an objective device but subjective questionnaires, across BMI ranges in a pediatric population.